Born Free and Equal?: A Philosophical Inquiry Into the Nature of Discrimination - Lippert-Rasmussen, Kasper (Oxford University Press, 2014)
What is discrimination? There are certain instances of differential treatment that almost anyone would describe as discriminatory; yet upon deeper examination, this near-unanimity gives way to disagreement and difference. For instance, is it discrimination when hospitals hire non-smokers only? Not only do people differ on which cases of differential treatment they see as discriminatory, they also disagree about when discrimination is morally wrong; what makes it morally wrong; and, indeed, about whether all forms of discrimination are morally wrong! Finally, many disagree over what should be done about wrongful discrimination-especially about what the state could permissibly do to eliminate wrongful discrimination, e.g. in people's love lives. This book addresses these issues. It argues that there are different concepts of discrimination and that different purposes pertaining to different contexts determine which one is the most useful. It gives special attention to a concept of discrimination that ties discrimination to differential treatment of people on the basis of their membership in socially salient groups. Second, it argues that when discrimination is wrong, it is so first and foremost because of its harmful effects. Third, it takes issue with some of the standard devices used to counteract discrimination and submits that combating discrimination requires more than state actions. Finally, it argues that states may sometimes permissibly discriminate. "[Lippert-Rasmussen] is a master of advancing discussion on a topic by showing that where the rest of us saw only two or three possible positions, there are many positions, often smeared together in a confused way in prior writings on the topic. The different views need to be carefully distinguished, and we then need to look carefully at what can be said for and against each in turn. When we do this, our view of the issues significantly shifts. This method and its fruits are evident throughout the bookEL [The] author's analytical skill and creative imagination in following through this method make the book a pleasure to read." -Richard J. Arneson, Professor of Philosophy, University of California, San Diego